Mapping a hospital using OpenStreetMap and Graphhopper: A navigation system - K. A. F. A. Samah; S. Ibrahim; N. Ghazali; M. Suffian; M. Mansor; W. A. Latif (Bulletin of Electrical Engineering and Informatics, 2020)
We present a mobile-based navigation system with the emphasis on the pedestrian navigation for Hospital Kuala Lumpur (henceforth, HKL) named as HKLNS. This practical research aimed to provide support and help for the people who come to the HKL. Despite having signages, layouts and other types of guidance to help them navigate, they might not be sure their current location and the destination’s paths. By using the OpenStreetMap (OSM) and Graphhopper API as a solution, it managed to help people to navigate the surrounding of the HKL. The findings showed that users were able to know their current location and the system generated the shortest pedestrian paths to the desired location using both mappings. The functionality testing and experimental results surrounding HKL demonstrated the effectiveness of this approach. The HKLNS was reliable based on the functionality and validation testing conducted towards 5 respondents with 5 different case study, in which it manage to reduce more than 50% time taken with the t-test result of 0.00041 (p less than 0.05), indicated that the system was accepted.